From Ecotourism to Regenerative Hospitality: Advancing Sustainable Tourism Development in Ghana and West Africa - Deri, Mildred Nuong; Zaazie, Perpetual; Dery, Jane; Ntow-Gyan, Kwame; Akubia, Yaa Mawufemor (Eco-Tourism and Sustainable Development, 2026)
Ecotourism has helped preserve biodiversity and provide jobs in Ghana and West Africa, but poor local management, ecological regeneration, and regulation are hindering its growth. This study examines how regeneration-focused hospitality might overcome structural hurdles in underdeveloped countries. A qualitative and literature synthesis research approach was used with peer-reviewed academic publications, local policies, and Ghanaian and West African ecotourism, sustainability, and regenerative tourism development studies to support the research. The analysis is combined with three main theories—regenerative development, sustainability science, and community-based tourism—and analysed thematically. According to this study's evidence, ecotourism global practices in the region have prioritised minimising negative impacts and complying with regulations over ecological regeneration, in-community co-creation, and value retention. To fill this gap, a complete framework for regenerative hospitality in ecologically diverse settings with institutional challenges in developing countries is offered. This framework includes ecological regeneration, landscape rehabilitation, community engagement, equitable land ownership distribution, culture regeneration, regenerative economy/business models, circular resource use, and local value development, and proactive multi-jurisdictional, multi-level governance. Regenerative hospitality in eco-lodges, resorts, and community-based tourism will improve climate resilience, youth employment, rural community support, and long-term destination viability. The research clarifies and guide ecotourism-regenerative hospitality links in West Africa.